4
$\begingroup$

Question in the title. Does $\sum_{n = 2}^{\infty} [\zeta(n) - 1]$ converge? If not, how about $\sum_{n = 1}^{\infty} [\zeta(2n) - 1]$?

$\endgroup$
4
$\begingroup$

About the first series:

$$ S=\sum_{n\geq 2}\left(\zeta(n)-1\right)=\int_{0}^{+\infty}\sum_{m\geq 1}\frac{x^m}{m!}\left(\frac{1}{e^x-1}-\frac{1}{e^x}\right)\,dx $$ leads to: $$ S = \int_{0}^{+\infty}(e^x-1)\left(\frac{1}{e^x-1}-\frac{1}{e^x}\right)\,dx = \int_{0}^{+\infty}e^{-x}\,dx = \color{red}{1}.$$

About the second series:

$$S= \sum_{n\geq 1}\left(\zeta(2n)-1\right) = \int_{0}^{+\infty}\sum_{m\geq 0}\frac{x^{2m+1}}{(2m+1)!}\left(\frac{1}{e^x-1}-\frac{1}{e^x}\right)\,dx$$ hence $$ S = \int_{0}^{+\infty}\frac{\sinh(x)}{e^x(e^x-1)}\,dx = \frac{1}{2}\int_{1}^{+\infty}\frac{u-\frac{1}{u}}{u^2(u-1)}\,du=\frac{1}{2}\int_{1}^{+\infty}\frac{u+1}{u^3}\,du=\color{red}{\frac{3}{4}}. $$ The same technique (i.e. to exploit the integral representation for the $\zeta$ function) works pretty well for similar problems, too.

$\endgroup$
  • $\begingroup$ Very cool, thank you. Can the same technique be used to find $\sum_{n = 1}^{\infty}[\zeta(mn) - 1]$ for an arbitrary positive integer $m$? I think it's interesting that these series of irrational numbers without any obvious pattern converge to such simple rational limits. $\endgroup$ – Vik78 Sep 17 '16 at 15:22
  • $\begingroup$ @Vik78: you may use the same technique to compute the generating function $$f(x)=\sum_{n\geq 2}(\zeta(n)-1)x^{n} $$ in terms of the dilogarithm. If you apply a discrete Fourier transform to the above generating function (i.e. compute its values at the $m$-th roots of unity) you may compute such generalized series, too. They won't have rational values for every $m\in\mathbb{N}$, however. $\endgroup$ – Jack D'Aurizio Sep 17 '16 at 15:30
6
$\begingroup$

The family $(n^{-k})$ with $n, k \ge 2$ is summable, because the geometric series gives us the estimation

$$\sum_{k=2}^N \sum_{n=2}^N \frac{1}{n^k} < \sum_{n=2}^N \sum_{k=2}^\infty \frac{1}{n^k} = \sum_{n=2}^N \frac{1}{n(n-1)} = 1 - \frac{1}{N} < 1.$$

Therefore we can exchange the order of summation and write

$$\sum_{k=2}^\infty (\zeta(k) - 1) = \sum_{n=2}^\infty \sum_{k=2}^\infty \frac{1}{n^k} = \sum_{n=2}^\infty \frac{1}{n(n-1)} = 1.$$

$\endgroup$
0
$\begingroup$

Figured out the solution:$\sum_{n=2}^{\infty} [\zeta(n) - 1] = \sum_{n=2}^{\infty}\sum_{k=2}^{\infty} n^{-k} = \sum_{n=2}^{\infty}\frac{1}{1-\frac{1}{n}} - 1 - \frac{1}{n} = \sum_{n=2}^{\infty}\frac{1}{n(n-1)}$, which converges by comparison with $\zeta(2)$.

$\endgroup$
  • $\begingroup$ The final sum converges to exactly $1$ (telescoping sum). $\endgroup$ – Erick Wong Sep 18 '16 at 19:36
0
$\begingroup$

$$0\le \zeta(n)-1=\frac{1}{2^n}+\sum_{k\ge3}\frac{1}{k^n}\le\frac{1}{2^n}+\int_2^\infty\frac{dx}{x^n}=\frac{1}{2^n}+\frac{1}{(n-1)2^{n-1}}=\frac{n+1}{n-1}\frac{1}{2^n}$$

which $\le\frac{3}{2^n}$ for $n\ge2$. Thus, the sum converges by comparison with the geometric series $\sum \frac{1}{2^n}$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.